Letter (copy) : International Brigade Dependants Fund - Bell, G.
034-0062-001 JB 15th July, 1939. Mr. G. Bell. 7, Princes Street, Corbridge, Northumberland. Dear Sir, INTERNATIONAL BRIGADE DEPENDANTS FUND. I have to acknowledge the receipt of your letter of 13th instant, together with postal order for 2s.0d, being a donation to the above Fund. I must point out that donations to the International Solidarity Fund are for the assistance of Spanish Workers only, and I am therefore returning your postal order in order that you may forward it to the Fund direct. Yours faithfully. Joint Secretary. Enc. 292/946/34/62